Direção teatral na perspectiva de Anne Bogart - Lodi, Fabiano [UNESP] (2015)
In the current research we investigate aspects related to the art of directing, emphasizing the artistic experience of Anne Bogart in the SITI Company - theater company founded in the United States in 1992. One of the characteristics of Bogart's work developed in SITI Company is about training: a current practice in many different artistic approaches in the theatre history concerning to continuous improvement of the actor's (and the actress's) techniques. Here the training is regarded as a concept which was established throughout the twentieth and twenty-first centuries under prerogatives conceived by theatre directors. In the SITI Company, the training is a combination of the Suzuki Method and the Viewpoints, two different theatrical techniques that overlap cultural references of East and West. We went under reflections on the procedures adopted by Bogart in the SITI Company, in order to specify a particular understanding of the links between the concept of training and the art of directing. And how it becames a proposition for Bogart relative to a director's role.